The Building Fabric Thermal Performance of Passivhaus Dwellings—Does It Do What It Says on the Tin? - David Johnston (Sustainability, 2016)
The Passivhaus (or Passive House) Standard is one of the world’s most widely known voluntary energy performance standards. For a dwelling to achieve the Standard and be granted Certification, the building fabric requires careful design and detailing, high levels of thermal insulation, building airtightness, close site supervision and careful workmanship. However, achieving Passivhaus Certification is not a guarantee that the thermal performance of the building fabric as designed will actually be achieved in situ. This paper presents the results obtained from measuring the in situ whole building heat loss coefficient (HLC) of a small number of Certified Passivhaus case study dwellings. They are located on different sites and constructed using different technologies in the UK. Despite the small and non-random nature of the dwelling sample, the results obtained from the in situ measurements revealed that the thermal performance of the building fabric, for all of the dwellings, performed very close to the design predictions. This suggests that in terms of the thermal performance of the building fabric, Passivhaus does exactly what it says on the tin.